2014
DOI: 10.1002/cbf.3024
|View full text |Cite
|
Sign up to set email alerts
|

Induction of foetal haemoglobin synthesis in erythroid progenitor stem cells: mediated by water‐soluble components of Terminalia catappa

Abstract: Current novel therapeutic agents for the treatment of sickle cell anaemia (SCA) focus on increasing foetal haemoglobin (HbF) levels in SCA patients. Unfortunately, the only approved HbF-inducing agent, hydroxyurea, has long-term unpredictable side effects. Studies have shown the potential of plant compounds to modulate HbF synthesis in primary erythroid progenitor stem cells. We isolated a novel HbF-inducing Terminalia catappa distilled water active fraction (TCDWF) from Terminalia catappa leaves that induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Recently, it is reported that an Indian almond, called Terminalia catappa , has long been used as a traditional herbal treatment for SCA in Nigeria [ 78 ]. Aimola et al has then demonstrated Terminalia catappa distilled water active fraction (TCDWF) from Terminalia catappa leaves exhibit a stimulatory effect on the HbF production in primary erythroid prohenitor stem cells (EPSCs) [ 77 ]. Terminalia catappa consists of flavonoids, alkaloids, and anthraquinones.…”
Section: Natural Remedies As Hbf Inducermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it is reported that an Indian almond, called Terminalia catappa , has long been used as a traditional herbal treatment for SCA in Nigeria [ 78 ]. Aimola et al has then demonstrated Terminalia catappa distilled water active fraction (TCDWF) from Terminalia catappa leaves exhibit a stimulatory effect on the HbF production in primary erythroid prohenitor stem cells (EPSCs) [ 77 ]. Terminalia catappa consists of flavonoids, alkaloids, and anthraquinones.…”
Section: Natural Remedies As Hbf Inducermentioning
confidence: 99%
“…Terminalia catappa consists of flavonoids, alkaloids, and anthraquinones. Also, through gas chromatography-mass spectrometry (GCMS), it is shown that a group of highly related long-chain fatty acids, for example, hexadecanoic acid, 10-octadecenoic acid, and octadecenoic acid, are present in the TCDWF [ 77 ]. Yet, further investigation is required in order to confirm the biological activities of these active compounds present in the TCDWF.…”
Section: Natural Remedies As Hbf Inducermentioning
confidence: 99%
“…Aimola et al [10] isolated a novel fetal hemoglobin-inducing compound ( T. catappa distilled water active fraction) from the leaves of T. catappa , which work synergistically, and recommended a dual modulatory effect on inherent erythropoiesis. Ratnasooriya et al [11] found that the extract form of tender leaves have anti-inflammatory as well as analgesic activities without affecting the estrous cycle, and also found that dosage does not induce sedation.…”
Section: Botanical Descriptionmentioning
confidence: 99%
“…Increase in RBC membrane CVA content has been shown to protect humans against coronary heart disease (Djoussé et al, 2012), However, very little is known about the link between CVA metabolism and hemoglobin expression. We have previously reported the fetal hemoglobin inducing activity of a water purified fraction of Terminalia catappa leaf extract on primary hematopoietic progenitor cells (Aimola et al, 2014). Further chromatographic studies on this fraction revealed that this fraction contained CVA (un-published data).…”
Section: Introductionmentioning
confidence: 95%